NON INVASIVE DELIVERY OF PROTEIN AND PEPTIDE DRUGS: A REVIEW - P.k.Lakshmi; D. PRASANTHI; B. VEERESH (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Till recent, injections remained the most common route for administration of protein and peptide drugs because of their poor bioavailability in the other routes. Because it is generally recognized that injection based delivery is a major impediment to the commercial success of therapeutic proteins and peptides, research in both academia and industry continues to focus on ways to overcome this problem. Possible non-parenteral administration routes for delivery of peptide and protein drugs include oral, nasal, ocular, transdermal, rectal, colonic, and vaginal route. The large surface area associated with most of these routes makes them attractive targets for drug delivery. While non-invasive administration by these routes is considered a more logical and achievable option for local treatment regimens, systemic delivery of proteins and peptides is significantly more challenging. In spite of effort made on the development of drugs for these routes, most of the successes fail to address how the technology will be transformed to a commercial product. The only notable exceptions have been the successful commercialization of nasal formulations for systemic delivery of a limited number of therapeutic peptides, and recent regulatory approvals of both pulmonary and buccal delivery systems for systemic delivery of insulin and an oral formulation of a small peptide analog, cyclosporine, have been commercialized. The present review aims to discuss the potential non-invasive routes of protein and peptide drug delivery. The factors which will affect drug transport and the bioavailability of proteins administered through these routes is also emphasized